Evaluation of municipal solid waste generation in selected water villages in Sabah, Malaysia - Alias, Fatma Sabariah (2014)
Life in the estuary and the beach is a unique settlement patterns in the history of Malaysia. Sabah is well known for its water village settlement that built on very high wooden pillars in estuarine and coastal water area. However, nowadays solid waste has become a serious problem especially in water village where the solid waste has stranded at the surrounding of the village area. Thus, the aim of this study is to evaluate municipal solid waste generation in the selected water villages in Sabah. The solid waste evaluation conducted at three different water villages which are Kampung Tanjung Batu Laut, Tawau; Kampung Tanjung Aru, Kota Kinabalu and Kampung Sim-Sim, Sandakan. There are about 150 households involved in solid waste generation and composition study while total of 242 respondents were involves in the survey study. Total solid waste generation was 1519.30 kg which the solid waste generation rate per household was 0.29 kg/person/day respectively. Almost 48% of respondents have discharge directly their waste into the sea. This is because by using a severity index the average of respondent knowledge is 77% but only 48% of respondent aware on the proper way in handling the solid waste. Furthermore, the results from the linear model revealed that attitude have significant relationship which influence the solid waste generation. Hence, the water villages should have an effective solid waste management in order to reduce bad impact to the environment and public health.